THE ROLE AND IMPORTANCE OF ENGLISH IN LEARNING MUSIC - Khudaynazarova M.A.,; Sattorova F.A, (Ustozlar uchun, 2025)
This article examines the growing importance and demand for English in music education. English is identified as a key factor in expanding musical knowledge, providing access to global resources, and enhancing opportunities for cultural exchange. Specifically, English proficiency is crucial for participating in music competitions, international festivals, and online learning platforms. Furthermore, English opens doors to career development and access to global networks, supporting musicians in achieving success. Consequently, mastering English emerges as essential for advancing in both music education and professional practice, underscoring its vital role in the modern musical landscape.